Online Determination of Sm, Eu and Yb in Environmental Samples by Inductively Coupled Plasma – Optical Emission Spectrometry - J. Dilip Kumar; P. Reddy Prasad; B. Krishna Priya; P. Subrahmanyam S. Ramanaiah; P. Chiranjeevi (E-Journal of Chemistry)
A procedure was developed for the determination of Sm, Eu and Yb in water samples by inductively coupled plasma-optical emission spectrometry (ICP-OES) after preconcentration on synthesized 5-(4-pyridyl azo)-8-quinolinol supported by Borassus flabellifer inflorescence (BFI). The sorbed element was subsequently eluted with 0.4 M HNO3 and the acid eluates were analyzed by ICP-OES. Under the optimal conditions, Sm, Eu and Yb in aqueous samples were concentrated 100-fold. Recoveries were obtained by the proposed method in the range of 98.6 -99.8%. This method was also applied for the analysis of spiked and natural water samples. The results provide strong evidence to support the hypothesis of an adsorption mechanism.